PENGARUH IMPLEMENTASI KEBIJAKAN PENDAFTARAN TANAH SISTEMATIS LENGKAP TERHADAP TERTIB PERTANAHAN DI KOTA BONTANG - Sandy Adma (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
This study aims to analyze the significant influence between the implementation of the Complete Systematic Land Registration policy on Land Order in the City of Bontang through the implementation of the PTSL policy, which is measured from the aspect approach: communication; resource; disposition; and bureaucratic structure. This research uses a quantitative method approach. The results showed that the implementation of the Systematic Complete Land Registration policy in the City of Bontang; well implemented in the aspects of communication, availability of resources, disposition, implementing policies, and aspects of the bureaucratic structure. The implementation of the Systematic Complete Land Registration policy in the City of Bontang has a positive impact on the creation of an orderly land law, seen from the decreasing number of land disputes and increased awareness of the people of the City of Bontang of the importance of an orderly land. Keyword : Complete Systematic Land Registration, Land Order